Research on energy consumption system of iron and steel enterprises with bottleneck. (2018) - Demin, Chen; Biao, Lu; Guang, Chen
For improving the energy utilisation efficiency of iron and steel enterprises, a systemic energy consumption analysis method was put forward in accordance with the index decomposition method of the e-p (IDM e-p) model. And this analysis method included that data collection of the enterprise; the improvement of the IDM e-p (IIDM e-p) model; partial correlation analysis (PCA) of energy consumption influencing factors in bottleneck location; multiple linear regressions (MLR) modelling in bottleneck position. And then, this systemic analysis method was used in an iron and steel enterprise. The analysis of the model showed that blast temperature and blast volume were key parameters on coke ratio in bottleneck location. The coke ratio decreased by 0.48 kg/t when the blast temperature was increased by 1% (2.15°C). When the blast volume was increased by 1% (7.93 m 3 /min), the coke ratio decreased by 0.43 kg/t.